PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN - Astari Dianty (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2019)
The purpose of this study was to examine the influence of intellectual capital (value added human capital, value added structural capital, and value added capitalemployed) of the financial performance be measured by return on asset (ROA) onbanking companies listed on the Bank Indonesia. The study period began in 2011 until 2012, with asampling method that is purposive sampling method. Statistical testing using multipleregression analysis. The results of partial showed that value added human capital has apositive effect and significant to return on asset, value added structural capital has apositive effect and significant to return on asset, whereas value added capital employedhas a negative effect and no significant to return on asset. The result of simultan showedthat value added human capital, value added structural capital, and value added capitalemployed have a positive effect and significant to return on asset.Keyword : Intellectual Capital, Financial Performance, Banking Company.